The Impact of Singing on Second Language Acquisition in Indonesian ESL Learners - Orun, Putri Anugraheli Ramba (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2023)
This quantitative study investigates the impact of singing songs on English as a Second Language vocabulary acquisition. Sixty Indonesian ESL learners were randomized into experimental and control groups, with the experimental group engaging in singing activities while the control group followed traditional instruction. Pre-test and post-test assessments in vocabulary, pronunciation, and translation were completed. The experimental group showed substantial gains across all metrics, including a 15.3 point vocabulary increase, 2.3 point pronunciation improvement, and 5.8 point translation enhancement (all p<0.001). Outcomes align with prior research on singing for language learning and support incorporating singing into ESL teaching to actively engage learners and improve linguistic skills. Limitations include short-term analysis and adult-focused sampling. Recommendations are longitudinal research, diverse participants, qualitative inquiries into experiences, and continued singing technique optimization.